2012
DOI: 10.1186/1471-2458-12-609
|View full text |Cite
|
Sign up to set email alerts
|

Case-finding of dementia in general practice and effects of subsequent collaborative care; design of a cluster RCT

Abstract: BackgroundIn the primary care setting, dementia is often diagnosed relatively late in the disease process. Case finding and proactive collaborative care may have beneficial effects on both patient and informal caregiver by clarifying the cause of cognitive decline and changed behaviour and by enabling support, care planning and access to services.We aim to improve the recognition and diagnosis of individuals with dementia in general practice. In addition to this diagnostic aim, the effects of case finding and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 31 publications
0
10
0
Order By: Relevance
“…Given the uncertainty regarding routine, population screening, targeted screening of people at risk for ADRD may represent an alternative to traditional population screening. 6 , 7 Patient characteristics, such as education and comorbidity burden, 8 , 9 as well as lifestyle factors, 10 have been shown to correlate with cognitive impairment screening results. For example, some research has shown that patients who score worse on cognitive assessment are more likely to be female, African-American, and have less years of formal education.…”
Section: Introductionmentioning
confidence: 99%
“…Given the uncertainty regarding routine, population screening, targeted screening of people at risk for ADRD may represent an alternative to traditional population screening. 6 , 7 Patient characteristics, such as education and comorbidity burden, 8 , 9 as well as lifestyle factors, 10 have been shown to correlate with cognitive impairment screening results. For example, some research has shown that patients who score worse on cognitive assessment are more likely to be female, African-American, and have less years of formal education.…”
Section: Introductionmentioning
confidence: 99%
“…Some studies show that more than 50% of persons with dementia have never received a diagnosis of dementia from a physician (7). A 2012 review showed that 14-33% of mild dementia and 28-61% of moderate to severe dementia cases were diagnosed in primary care (8)(9)(10)(11). In the short-term, timely diagnosis ensures access to psychosocial and pharmacological interventions .…”
Section: Introductionmentioning
confidence: 99%
“…FPs performed this classification of cognition based on their recollection of clinical patient contacts and on information in the electronic medical records. As described in a previous paper, this yielded a selection of persons with a prior chance of cognitive impairment of 47.1% (according to the CAMCOG), which is substantially higher than in the general population of this age [ 46 ].…”
Section: Methodsmentioning
confidence: 99%
“…Further management of persons diagnosed with MCI and having unmet care needs, or persons diagnosed with dementia, included psychoeducation, a needs assessment, drawing up of a care plan and referral to services. More details of the intervention are provided elsewhere [ 46 ].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation